A SHORT NOTE ON BANDS OF GROUPS - Davvaz, Bijan (Journal of the Indonesian Mathematical Society, 2015)
In this paper we give necessary and sufficient conditions on a semigroup S that it be semilattice of groups, a normal band of groups, and a matrix of groups.DOI : http://dx.doi.org/10.22342/jims.21.1.151.19-23